Impact of Pakistani Geo and Hum TV Dramas on Language and Dressing of Women - Qureshi, Muhammad Sher Dil; Mehmood, Hayyah; Irfan, Faisal; Fatima, Shehnaz (Pakistan Journal of Humanities and Social Sciences, 2023)
This research uses a survey as a data gathering instrument to look into the "Impact of Pakistani Geo and Hum TV Dramas on Language and Dressing of Women”. This study is quantitative by nature. It targeted 400 men and women between the ages of 20 and 45 watching Geo and Hum programs on Television. The findings suggested that Geo and Hum TV dramas impacted women's language and attire. The hypothesis was put to the test using the chi-square statistical test. The percentage and frequency of answers were calculated using SPSS Software. The impact of Geo and Hum TV programs on women was studied using the Cultivation Theory. Results of the study show that mass media, particularly Television, has the most substantial effects on its viewers' habits. The influence of Geo and Hum TV dramas on women has impacted a lot since the arrival of cable and satellite communications. Private channels are a source of change in women’s lifestyles.